Aspects of economic activity in Phoenicia during Roman and Byzantine times. The case of olive oil and amphora production in Chhim, in the chora of Sidon. (2nd September 2019) - Wicenciak, Urszula
Abstract : Using archaeological data from two closely located sites within the Sidon chora, Chhim and Jiyeh, the author considers possible oil distribution routes in Phoenicia in the Roman–Byzantine period, taking into account the impact, on this, of the administrative fragmentation of the region between the 1st and 7th centuries AD. A typology of, and data on, local and imported amphora from Chhim are presented. Various models are proposed in order to explain what appears, based on calculations relating to the output of the presses, a surplus of oil for which no corresponding evidence for exports — in the form of Chhim amphorae — can be identified. These include: alternative packaging for the oil (skins; Jiyeh amphorae-Beirut imitations); non-continuous, ad-hoc seasonal production; possible alternative markets, including Chhim's role and context in the road networks connecting the coast, Chhim and the Beqaa Valley.